(untitled) (Legal journal - Research in Legal and Social Sciences, 2017)
The present investigation has as its starting point the obstruction of criminal proceedings in which acts of corruption were investigated and then the acts of telephone communications interventions carried out within the framework of the process were declared unconstitutional, although they have provided relevant data for the beginning. formal criminal prosecution. Wiretapping, wiretapping or interception, along with the interception of correspondence, hidden cameras, among others, are auxiliary methods for the incorporation of elements of knowledge in criminal investigation. However, despite the progress they bring to the effectiveness of criminal prosecution, there is also the danger that the abusive or indiscriminate use of these methods imply an outrage on the privacy of the subjects subjected to the process. This allows us to pose the question about what would be the requirements that must be met in the prosecutor’s investigation to intervene or interfere with the telephone communications of the suspect, that is, what are the parameters that the authority in charge of granting permission to sacrifice the property should take into account. privacy of the suspect in the interest of the search for the truth.